Subject-Thematic and Artistic-Figurative Features of Early New Realism in Chinese Painting (Late 1980s – Early 1990s) - Liu, Haotian (HUDPROM: The Ukrainian Art and Design Journal, 2024)
This article explores the subject matter, thematic repertoire, and artistic-stylistic characteristics of early New Realism in Chinese painting (late 1980s – early 1990s). It examines the movement within the broader context of its thematic diversity and stylistic influences, including magical realism, rural realism, photorealism, and hyperrealism. The study establishes that New Realism in Chinese painting emerged as a synthesis of traditional realist approaches and innovative artistic explorations, reflecting the social and cultural transformations in China following the Cultural Revolution (1966–1976). The movement’s leading figures – Wang Yidong, Liu Yi, Leng Jun, and Shi Chong – built upon classical realist techniques while incorporating elements of folk culture, ethnographic motifs, and the symbolic language of traditional Chinese art. An analysis of these artists’ early works (late 1980s – early 1990s) reveals a shift in portrait and narrative painting, moving away from the conventions of socialist realism. Their paintings emphasize an intimate focus on the individual, exploring inner worlds and traditional ways of life. Unlike Western realism, Chinese New Realism integrates elements of romanticization and idealization, resonating deeply with traditional Chinese philosophical and aesthetic principles.